Wellbeing explained - Mainstone-Cotton, Sonia (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"Nurturing children and supporting their wellbeing is vitally important along with looking after the wellbeing of the staff who support them. Wellbeing Explained highlights the importance of wellbeing and explains key terms associated with wellbeing and mental health needs. Unpicking terms such as holistic development, self-esteem, SEMH and anxiety, it uses practical examples and case studies to explain what these mean and how we can promote wellbeing through policy and practices. Divided into two parts, the first provides a brief overview of the key terms associated with wellbeing in early childhood alongside examples of what they mean in practice. Part two then shares the principles that underpin promoting good wellbeing such as prioritising staff wellbeing, adopting a loving pedagogy, keeping the child and family central to provision, and creating an enabling environment explaining the underlying ethos of a child-centred approach. Part of the Key Concepts in Early Childhood Series, this is essential reading for early years practitioners and students that want to know and understand what they can do to support their own wellbeing and the children they work with"--
Anxiety -- ACEs -- Attachment needs -- Creativity/imagination -- Depression -- Dysregulation -- Early intervention -- Emotional regulation -- Emotional literacy -- Enabling environment -- Fight/ flight/freeze/fawn -- Holistic development -- Listening to children -- Loving pedagogy -- Leuven scale -- Joyfulness -- Mental health first aid -- Nature deficit disorder -- Nurture -- Outdoors -- SEMH -- Self-compassion -- Self-harm -- Self-esteem -- Selective Mutism -- Self-regulation -- Spiritual wellbeing -- Stress -- SSTEW scale -- Thrive -- Transitions -- Wellbeing -- Window of tolerance -- The rights of the child in relation to wellbeing -- The role of the adult in relation to wellbeing -- How the adult can prioritise their and their colleagues wellbeing -- How we can create an enabling environment which promotes wellbeing -- How we can engage parents and work in partnership with them when supporting their -- Children's wellbeing -- How to write a wellbeing policy -- Signposting for further advice -- Staff training.
Keywords: Early childhood education -- Great Britain; Early childhood education -- Psychological aspects; Preschool children -- Psychology; Early childhood teachers -- Psychology; Child mental health -- Great Britain; Well-being -- Great Britain; EDUCATION / Preschool & Kindergarten; EDUCATION / Elementary; EDUCATION / Professional Development